EXPLORING GENDER PERSPECTIVES IN ENGLISH LANGUAGE LEARNING AMONG INFORMATICS STUDENTS - Selamat Husni Hasibuan; Prima Yanti Siregar; Heridayani Heridayani; Wariyati Wariyati (Pusat Studi Gender dan Anak, 2026)
This study explores gender perspectives in English language learning among informatics students in a vocational higher education context. The research aims to examine how gender influences students’ participation, confidence, and use of technology in learning English. A qualitative approach with an exploratory design was employed to gain in-depth insights into students’ experiences and perceptions. Data were collected through semi-structured interviews, classroom observations, and documentation involving 12 students selected through purposive sampling, consisting of six male and six female participants. The data were analyzed using thematic analysis to identify key patterns and themes. The findings reveal that gender influences students’ engagement in English language learning, particularly in classroom participation, confidence in language use, and preferences in utilizing digital learning tools. Female students tend to demonstrate higher participation and confidence in communicative activities, while male students are more likely to experience anxiety and engage less in verbal interaction. In terms of technology use, male students tend to adopt a more instrumental approach, whereas female students prefer interactive and skill-based learning strategies. However, the study also finds that these differences are not absolute, as individual and contextual factors significantly shape students’ learning experiences. This study contributes to the literature by providing a qualitative understanding of gender dynamics in a vocational and technology-based educational setting. The findings suggest the importance of adopting inclusive and gender-responsive teaching practices to support diverse learner needs in English language classrooms. Keywords: Gender Perspectives, English Language Learning, Informatics Students, Classroom Participation